PENGARUH PENGALAMAN DAN PERSEPSI KUALITAS SERTA NILAI TERHADAP KEPUASAN DAN IMPLIKASINYA P - Juswanto Juswanto (Jurnal Riset Bisnis Indonesia, 2014)
The purpose of this study is to describe and analyze the influence of experience, and perception ofquality, and the value of the satisfaction and satisfaction with the word of mouth on the Blackberrymobile phone users Students Islamic University of Sultan Agung Semarang. This type of researchis quantitative. Data collection methods used were using questionnaire and interviews withrespondents, who took a sample of 100 respondents, using purposive sampling technique. The dataanalysis technique used is to use multiple regression analysis with SPSS 16.0 software. Resultsof research conducted showed that there was no significant effect of experience on customersatisfaction. perceived quality have a significant effect on satisfaction, perception of value had nosignificant effect on satisfaction, and satisfaction significantly influence customer’s word of mouth onBlackberry mobile phones. The implication is that word of mouth is a highly efficient means for thecompany, however word of mouth can not happen if there is no customer satisfaction. It is necessaryto secure the quality or innovation of products and the diversity of the features contained in theproduct Blackberry and more on fashion, which is able to give satisfaction in order to build positiveemotions in the minds of the customers in order to improve sales of the Blackberry .Keywords : experience, perceived quality, perceived value, and satisfaction, as well as word ofmouth .